Dampak Pertambangan Batubara terhadap Kondisi Sosial Ekonomi Masyarakat Desa Karang Indah Kecamatan Angsana Kabupaten Tanah Bumbu - Hidayanti, Yeni; Pahlevi, Khairi (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the impact of coal mining on the socio-economic conditions of the people of Karang Indah Village, Angsana District, Tanah Bumbu Regency. Data collection techniques include structured interviews with several respondents, as many as 91 KKthe data analysis technique using the triangulation technique. The social impact of coal mining is related to social interaction and cooperation. The negative impact of competition and conflict or dispute is also called the conflict in society itself, and society becomes individualistic. The positive impact is that public education is increasing. The economic impact that is felt is increasing the quality of human resources, increasing the economic income of the surrounding community, meeting the needs of miners, and reducing the unemployment and crime rates. Meanwhile, the negative impact that is felt is damaging the surrounding environment, damaging roads due to coal transportation by trucks, and decreasing soil fertility